Improving Medication Adherence in Patients with Hypertension: A Randomized Trial - Hedegaard, Ulla; Kjeldsen, Lene Juel; Pottegård, Anton; Henriksen, Jan Erik; Lambrechtsen, Jess; Hangaard, Jørgen; Hallas, Jesper (The American journal of medicine, 2015)
In patients with hypertension, medication adherence is often suboptimal, thereby increasing the risk of ischemic heart disease and stroke. In a randomized trial, we investigated the effectiveness of a multifaceted pharmacist intervention in a hospital setting to improve medication adherence in hypertensive patients. Motivational interviewing was a key element of the intervention. Patients (n = 532) were recruited from 3 hospital outpatient clinics and randomized to usual care or a 6-month pharmacist intervention comprising collaborative care, medication review, and tailored adherence counseling including motivational interviewing and telephone follow-ups. The primary outcome was composite medication possession ratio (MPR) to antihypertensive and lipid-lowering agents, at 1-year follow-up, assessed by analyzing pharmacy records. Secondary outcomes at 12 months included persistence to medications, blood pressure, hospital admission, and a combined clinical endpoint of cardiovascular death, stroke, or acute myocardial infarction. At 12 months, 20.3% of the patients in the intervention group (n = 231) were nonadherent (MPR <0.80), compared with 30.2% in the control group (n = 285) (risk difference -9.8; 95% confidence interval [CI], -17.3, -2.4) and median MPR (interquartile range) was 0.93 (0.82-0.99) and 0.91 (0.76-0.98), respectively, P = .02. The combined clinical endpoint was reached by 1.3% in the intervention group and 3.1% in the control group (relative risk 0.41; 95% CI, 0.11-1.50). No significant differences were found for persistence, blood pressure, or hospital admission. A multifaceted pharmacist intervention in a hospital setting led to a sustained improvement in medication adherence for patients with hypertension. The intervention had no significant impact on blood pressure and secondary clinical outcomes.